2019
DOI: 10.1002/uog.20180
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of partial amniotic carbon dioxide insufflation with cold, dry vs heated, humidified gas in a sheep model

Abstract: Objective Partial amniotic carbon dioxide (CO 2 ) insufflation (PACI) is used to improve visualization and facilitate complex fetoscopic surgery. However, there are concerns about fetal hypercapnic acidosis and postoperative fetal membrane inflammation. We assessed whether using heated and humidified, rather than cold and dry, CO 2 might reduce the impact of PACI on the fetus and fetal membranes in sheep. Methods Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 30 publications
2
57
2
Order By: Relevance
“…To conclude, the work of Amberg and colleagues supports the use of heated and humidified, rather than cold and dry, CO 2 gas for uterine insufflation during fetoscopic MMC repair. This alternative approach is likely to mitigate the detrimental metabolic effects of using cold, dry gas, with reduced inflammation in the fetal membranes.…”
Section: The Standard Of Care: Open‐hysterotomy Myelomeningocele (Mmcmentioning
confidence: 96%
See 3 more Smart Citations
“…To conclude, the work of Amberg and colleagues supports the use of heated and humidified, rather than cold and dry, CO 2 gas for uterine insufflation during fetoscopic MMC repair. This alternative approach is likely to mitigate the detrimental metabolic effects of using cold, dry gas, with reduced inflammation in the fetal membranes.…”
Section: The Standard Of Care: Open‐hysterotomy Myelomeningocele (Mmcmentioning
confidence: 96%
“…Amberg et al ,. in this issue of the Journal, present a well‐designed study performed on pregnant ewes with the objective of assessing whether using heated, humidified CO 2 for uterine insufflation would have less metabolic impact on the sheep fetuses, with reduced signs of inflammation in the fetal membranes.…”
Section: The Standard Of Care: Open‐hysterotomy Myelomeningocele (Mmcmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work demonstrated that this can be mitigated by maternal hyperventilation, along with heating and humidifying the gas. 40,41 Dry CO 2 also has an effect on the fetal membranes but, based on biomechanical studies published this year, heating and humidifying the gas may also reduce the risk for membrane rupture. 42,43 While the debate continues over whether or not minimally invasive surgery is equally neuroprotective as open surgery and which surgical techniques have the least prematurity risk, [44][45][46] it is worth considering the experience required to complete the learning curve for prenatal spina bifida repair.…”
Section: Advances In Fetal Theraphymentioning
confidence: 99%